Colonial Survey and Native Landscapes in Rural South Africa, 1850 - 1913 The Politics of Divided Space in the Cape and Transvaal - Braun, Lindsay F. (African Social Studies Series, 2015)
In Colonial Survey and Native Landscapes in Rural South Africa, 1850 - 1913, Lindsay Frederick Braun explores the technical processes and struggles surrounding the creation and maintenance of boundaries and spaces in South Africa in the nineteenth and early twentieth centuries.; Readership: Anyone interested in rural South Africa during the late nineteenth century, especially the Transkei or Transvaal, or the history of geography and survey relative to colonial states generally.